2013
DOI: 10.1109/tcomm.2013.091813.130127
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Alltop Functions that are EA-Inequivalent to the Cubic Function

Abstract: Sequences with optimal correlation properties are much sought after for applications in communication systems. In 1980, Alltop (IEEE Trans. Inf. Theory 26(3):350-354, 1980) described a set of sequences based on a cubic function and showed that these sequences were optimal with respect to the known bounds on auto and crosscorrelation. Subsequently these sequences were used to construct mutually unbiased bases (MUBs), a structure of importance in quantum information theory. The key feature of this cubic function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In fact we can show Proposition 4. (See [16,19]) If 1 ≤ a < d, d is an odd prime, and g is as in (11), then…”
Section: 2mentioning
confidence: 99%
“…In fact we can show Proposition 4. (See [16,19]) If 1 ≤ a < d, d is an odd prime, and g is as in (11), then…”
Section: 2mentioning
confidence: 99%
“…These order 3 unitaries appear in the orbit complete MUBs construction, too. As a consequence of the orbit complete MUBs lying in different Clifford orbits in dimension N = 3k + 1 [28], the Alltop fiducial vectors in Equation ( 16) must be left invariant by more Clifford unitaries than the one used in Equation (21). The additional unitaries that leave the fiducial invariant are the order 3 elements in the SIC problem.…”
Section: Appendix: Orbit Complete Mubs and Sicsmentioning
confidence: 99%
“…Alltop's original paper was motivated by classical signal processing, but the functions were shown to lead to complete MUBs in prime and odd prime power dimensions [20]. Recently, a new family of Alltop functions was found [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent illustration of this appears in [15] where it is shown that for p ≥ 5 and m an integer that does not divide p m + 1, then the function f (x) = x p m +2 over Z m p is an Alltop function (that is, its differential functions are PN) which is EA-inequivalent to the Alltop function f (x) = x 3 , even though ∂f and ∂f are EA equivalent PN functions.…”
Section: The Case G = Zmentioning
confidence: 99%
“…According to [19] there are 5 EA equivalent classes of differentially 4-uniform permutations, and as they all have different extended Walsh spectra, they each form a single CCZ equivalence class. On the other hand, using MAGMA [3] and checking all differentially 4-uniform permutations in S 15 , there are exactly 10 CCZ equivalence classes, given by the following permutations: [19]), σ 5 = (5, 6, 8) (7,11,14,10,12,13), σ 6 = (5, 6, 8)(7, 11, 14)(10, 12, 13) (= f 7 in [19]), σ 7 = (5, 6, 8)(7, 11, 13, 15)(9, 12, 10), σ 8 = (5, 6, 8)(7, 11, 13)(9, 12, 14, 10), σ 9 = (5, 6, 8) (7,11,13,10,9,12,14), σ 10 = (5, 6, 8)(7, 11) (9,12,10,13,15,14) . Table 4 corrects [19, Table 2], where the CCZ classes of σ 1 , σ 2 , σ 3 , σ 4 , σ 6 were claimed to exhaust the differentially 4-uniform classes of permutations fixing 0 over Z 4 2 .…”
Section: Differentially 4-uniform Permutationsmentioning
confidence: 99%